2004
DOI: 10.1016/j.jmaa.2004.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Some geometric properties in modular spaces and application to fixed point theory

Abstract: We prove that modular spaces L ρ have the uniform Kadec-Klee property w.r.t. the convergence ρ-a.e. when they are endowed with the Luxemburg norm. We also prove that these spaces have the uniform Opial condition w.r.t. the convergence ρ-a.e. for both the Luxemburg norm and the Amemiya norm. Some assumptions over the modular ρ need to be assumed. The above geometric properties will enable us to obtain some fixed point results in modular spaces for different kind of mappings.  2004 Elsevier Inc. All rights rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…(H2) ∆ 2 -type condition: A modular ρ is said to satisfy the ∆ 2 -type condition [45,46] if there exists k > 0 such that ρ(2x) ≤ kρ(x) for all x ∈ X ρ . (H3)s-convex modulars: If condition (3) in the modular definition is replaced by ρ(αx + βy) ≤ αsρ(x) + βsρ(y) for all α, β ∈ [0, ∞) with αs + βs = 1 with ans ∈ (0, 1], the modular ρ is called ans-convex modular [22]. In particular, a 1-convex modular is simply called convex.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…(H2) ∆ 2 -type condition: A modular ρ is said to satisfy the ∆ 2 -type condition [45,46] if there exists k > 0 such that ρ(2x) ≤ kρ(x) for all x ∈ X ρ . (H3)s-convex modulars: If condition (3) in the modular definition is replaced by ρ(αx + βy) ≤ αsρ(x) + βsρ(y) for all α, β ∈ [0, ∞) with αs + βs = 1 with ans ∈ (0, 1], the modular ρ is called ans-convex modular [22]. In particular, a 1-convex modular is simply called convex.…”
Section: 3mentioning
confidence: 99%
“…Some excellent overviews of (H1)-(H4) conditions are provided in [27,22,54]. It is shown that a modular ρ implies that…”
Section: 3mentioning
confidence: 99%
“….s-convex modular [39]: If condition (3) in the modular definition is replaced by ρ(αx + βy) ≤ αsρ(x) + βsρ(y) for all α, β ∈ [0, +∞) with αs + βs = 1 with ans ∈ (0, 1], the modular ρ is called ans-convex modular. In particular, a 1-convex modular is simply called convex.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…In 1990, Khamsi et al [7] initiated the study of fixed point theory for nonexpansive mappings defined on some subsets of modular function spaces. More researches on fixed point theory in modular function spaces can be found in [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%